STATISTICAL ANALYSIS OF SPATIAL DIFFERENTIATION OF THE PENSION SYSTEM INCOME - Svetlana S. Mikhaylova (Статистика и экономика, 2016)
The article offers the methodical approach to differentiation measurement of the subjects of the Russian Federation on the level of receipt of insurance premiums on mandatory pension insurance. Discrepancy of regions distribution on a studied indicator to the normal law is revealed. The procedure of normalization of an indicator is carried out, the statistical group of subjects of the Russian Federation on level of the obligatory level income of the pension system is constructed, the social and economic characteristic of the allocated groups of regions is given.